Essential Japanese Vocabulary : Learn To Avoid Common (And Embarrassing!Rpara Mistakes - Miura, Akira (Tuttle Publishing, 2013)
This is a clear, simple and compact guide to colloquial, everyday Japanese. - Acquire basic proficiency in spoken Japanese. - A streamlined, efficient approach. - Perfect for self-learners or classroom use. - Includes kanji and kana. Essential Japanese Vocabulary teaches all the Japanese grammar you need to speak and understand simple spoken Japanese. Covering only what is essential, it provides and efficient way for learners who have limited time to gain basic proficiency and begin to communicate naturally with Japanese language speakers. Intended for both self-study and classroom use the guide offers a practical course in colloquial Japanese, but leaves aside forms that are unnecessary or little used as well as those that are more important for written Japanese. In short chapters, it helps the user understand the logic of Japanese grammar, while its straightforward explanations and clear examples make learning as easy as possible. The book includes a glossary of grammatical terms and an index, as well as appendixes on Japanese pronunciation and verb conjugation. In a focused and convenient approach, Essential Japanese Vocabulary is an indispensable tool for beginners just starting to learn Japanese or a handy aid for more experience learners who wish to refresh their knowledge.